Investigation of piperazine benzamides as human β3 adrenergic receptor agonists for the treatment of overactive bladder. Issue 4 (15th February 2017) - Harper, Bart H.; Wang, Liping; Zhu, Cheng; Kar, Nam F.; Li, Bing; Moyes, Christopher R.; Goble, Stephen D.; Costa, Melissa; Dingley, Karen; Di Salvo, Jerry; Ha, Sookhee N.; Hurley, Amanda; et al.
Graphical abstract: Abstract: The synthesis of a novel class of piperazine benzamide (reverse amides) targeting the human β3 -adrenergic receptor for the treatment of overactive bladder (OAB) is described. The SAR studies directed towards maintaining well established β3 potency and selectivities while improving the overall pharmacokinetic profile in the reverse amide class will be evaluated. The results and consequences associated with functional activity at the norepinephrine transporter (NET) will also be discussed.